2008
DOI: 10.1037/a0013022
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent change language within a brief motivational intervention and substance use outcomes.

Abstract: The notion that client language about change is related to actual behavioral change is central to the practice of motivational interviewing (MI), but has not been examined in adolescent clients. In this study homeless adolescents who used alcohol or illicit substances but were not seeking treatment (n = 54) were recorded during brief motivational interventions. Adolescent language during sessions was coded based on MI concepts, and ratings were tested as predictors of rates of substance use over time. Types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 20 publications
4
119
1
Order By: Relevance
“…However, findings from the therapeutic context underscore the predictive nature of change talk for future actions (Aharonovich et al, 2008;Amrhein et al, 2003;Baer et al, 2008;Gaume et al, 2008;Hodgins, Ching, & McEwen, 2009). Future research should explore whether employee change talk similarly predicts behavioural change in organizational settings.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, findings from the therapeutic context underscore the predictive nature of change talk for future actions (Aharonovich et al, 2008;Amrhein et al, 2003;Baer et al, 2008;Gaume et al, 2008;Hodgins, Ching, & McEwen, 2009). Future research should explore whether employee change talk similarly predicts behavioural change in organizational settings.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The original language categorization into desire and ability originates from psycholinguistic laboratory studies using quasi-performative verbs (Amrhein, 1992). This categorization has been extended in therapy field research integrating commitment (Mahrer, Gagnon, Fairweather, Boulet, & Herring, 1994), reasons, need, and taking steps (Aharonovich et al, 2008;Amrhein et al, 2003;Baer et al, 2008) and is incorporated within the observation coding manuals for MI (Martin, Moyers, Houck, Christopher, & Miller, 2005;Miller & Mount, 2001;Miller et al, 2008). Whereas earlier MI coding manuals could only predict the lack of behaviour change based on resistance language (i.e.…”
Section: Recipient Behaviours In Change Conversationsmentioning
confidence: 99%
“…In terms of candidates for within-session active ingredients, in contrast with other putative mechanisms (Apodaca and Longabaugh, 2009;Longabaugh and Wirtz, 2001), change talk (client statements in favor of change) has gained the most consistent support for its relationship with substance use outcomes across MI (Amrhein et al, 2003;Apodaca and Longabaugh, 2009;Baer et al, 2008;Daeppen et al, 2010;Gaume et al, 2008;Martin et al, 2011;Moyers et al, 2007Moyers et al, , 2009Strang and McCambridge, 2004;Vader et al, 2010;Walker et al, 2011), as well as across other psychosocial interventions (Aharonovich et al, 2008;Hodgins et al, 2009;Karno et al, 2010;Moyers et al, 2007). Together, these data suggest that change talk is the most relevant target for mechanism research in MI (Miller and Rose, 2009), and it therefore serves as the focus of this review.…”
Section: Within-session Processesmentioning
confidence: 99%
“…Research has shown a correlation between change talk and improved patient outcomes (Baer et al, 2008, Gaume et al, 2008.…”
Section: The Principles Of MImentioning
confidence: 99%